Peningkatan Produktivitas Pengusaha Kerupuk Mlarat melalui Perancangan Mesin Pengulen dan Pemotong Adonan - Purwo Kadarno; Iwan Sukarno; Harummi Sekar Amarilies; E Byan Wahyu Riyandwita; Aurilius Oberman Manurung; Khusnun Widiyati; Yudha Purbolaksono (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
Kerupuk Mlarat is one of the traditional snacks of Cirebon, a regency in West Java province, Indonesia. This snack is mostly produced by the small medium enterprises (SMEs) through conventional, old-style procedures. That is why, although this snack has abundant potentials, the improvement is still minimum. Most SMEs employ human-powered tools, especially in the process of dough kneading and shaping. Besides the not yet optimum process, the food hygiene of also becomes an issue. In order to optimize the production and maintain product hygiene, a human empowerment program is conducted to provide on of the SMEs with the Kerupuk Mlarat dough kneading and shaping machine. The machine capacity is 20 kilograms and was proven effective to knead, shape, and cut the dough within an hour, a lot less duration compared to the conventional procedures. This machine is expected to efficiently improve the Kerupuk Mlarat SMEs productivity as well as hygiene.